PENERAPAN PASAL 4 HURUF H UNDANG - UNDANG NO 8 TAHUN 1999 PERLINDUNGAN KONSUMEN TERKAIT HAK UNTUK MENDAPATKAN KOMPENSASI PADA TRANSAKSI JUAL BELI ONLINE TIKTOK SHOP PERSPEKTIF HUKUM BISNIS SYARI’AH - Umi Habibatul Mu thiyyah; Islami, Trinah Asi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The author conducted a study titled "Application of Article 4 Letter H of Law No. 8 of 1999 Consumer Protection Regarding the Right to Compensation in Online Trading Transactions on TikTok Shop from the Perspective of Sharia Business Law." This study aims to answer two questions: how the application of Article 4 of Law No. 8 of 1999 on Consumer Protection concerning the right to compensation in online trading transactions on the TikTok shop and also regarding the right to compensation in online trading transactions on the TikTok shop from the perspective of Sharia business law.This study discusses the application of Article 4 Letter H of Law No. 8 of 1999 on Consumer Protection in the context of the right to compensation in online trading transactions on TikTok Shop from the perspective of Sharia Business Law. The research method used is normative juridical with a descriptive analytical approach.This study uses empirical juridical research. Data collection techniques include observation, interviews, documentation, and literature study. The data sources in this study are primary data and secondary data. The data analysis techniques used are inductive and descriptive data analysis methods.The results of the study indicate that the application of Article 4 H of Law No. 8 of 1999 still has many weaknesses in ensuring optimal consumer protection in online trading transactions on TikTok Shop, particularly in the context of Sharia business law. Some of the challenges faced include the lack of awareness of consumer rights based on Sharia law and the lack of regulations governing Sharia-based online transactions.Proposed solutions include increasing consumer awareness of their rights based on Sharia principles and the need for stricter regulations on Sharia-based online transactions. This study is expected to contribute to strengthening consumer protection in online purchasing transactions by taking into account Sharia values in business law.